2014
DOI: 10.1002/pi.4678
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of poly[(butyl methacrylate)‐co‐(butyl acrylate)] via activator regenerated by electron transfer atom transfer radical polymerization: insights and improvement

Abstract: The copolymerization of butyl methacrylate and butyl acrylate initiated by CuBr 2 /tris[(2-pyridyl)methyl]amine/ethyl 2-bromoisobutyrate, with tin(II) 2-ethylhexanoate as reducing agent, is studied experimentally and using kinetic Monte Carlo simulations at 70 and 90• C under batch activator regenerated by electron transfer atom transfer radical polymerization conditions in anisole at low Cu levels (down to 35 ppm Cu on a molar basis with respect to monomer). With increasing initial butyl acrylate content, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…For example, the extremely active photoexcited catalyst (Cat à ) can either reduce the alkyl halogen or decay to the ground state catalyst (Cat). 19,20,31,33,[48][49][50][51] As in those metal-catalyzed ATRP systems, the catalyst is in high-oxidation-state at the beginning of the reaction, and the deactivation effect is strong during the entire polymerization. As a result, the concentration of deactivator is low at the early stage of polymerization, as shown in Figure 2A.…”
Section: Reactant Concentrations and Reaction Rates For O-atrpmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the extremely active photoexcited catalyst (Cat à ) can either reduce the alkyl halogen or decay to the ground state catalyst (Cat). 19,20,31,33,[48][49][50][51] As in those metal-catalyzed ATRP systems, the catalyst is in high-oxidation-state at the beginning of the reaction, and the deactivation effect is strong during the entire polymerization. As a result, the concentration of deactivator is low at the early stage of polymerization, as shown in Figure 2A.…”
Section: Reactant Concentrations and Reaction Rates For O-atrpmentioning
confidence: 99%
“…[11][12][13][14][15] This characteristic for O-ATRP systems is different from other improved ATRP techniques, such as activators regenerated by electron transfer (ARGET) ATRP or electrochemically mediated ATRP (eATRP). 19,20,31,33,[48][49][50][51] As in those metal-catalyzed ATRP systems, the catalyst is in high-oxidation-state at the beginning of the reaction, and the deactivation effect is strong during the entire polymerization. While the ground-state catalyst (Cat) initially exists in O-ATRP system, is a poor oxidant without deactivation effect.…”
Section: Reactant Concentrations and Reaction Rates For O-atrpmentioning
confidence: 99%
“…This difference in the activation kinetics of initiator and dormant chains was applied by Payne et al. to model the ARGET‐ATRP of BMA and provide good agreement between the experimental and simulation results. As this work utilizes the same monomer BMA, ATRP initiator EBiB, Cu(I)Br as the catalyst in the activation reaction, and anisole as the solvent, the same k a ,0 value of 3.25 L·mol −1 ·s −1 at 70 °C is used.…”
Section: Resultsmentioning
confidence: 99%
“…However, the addition of a low amount of BA in the system gives rise to a remarkable decrease in the M n with higher dispersity values. 26 Recently, Ribelli et al 27 reported the contribution of the bimolecular reaction termination and the catalytic radical termination (CRT) in the polymerization of methyl acrylate (MA) via ATRP using Cu 2 Br (pMA-Br) with several ligands: TPMA, tris [2-(dimethylamino)ethyl]amine (Me 6 TREN), and tris(3,5-dimethyl-4-methoxy-2-pyridylmethyl) (TPMA* 3 ). By using size exclusion chromatography (SEC), the MWD of the polymers obtained from the activation of the pMA-Br macroinitiator in more conventional radical conditions exhibited a bimodality, concluding that the higher molecular weight population corresponds to dead chains predominantly obtained by termination by combination for acrylate systems.…”
Section: Introductionmentioning
confidence: 99%
“…Payne et al 26 used a kinetic Monte Carlo (kMC) method in the study of BA and BMA in ARGET ATRcoP; the modeling results helped to understand the influence of the BA addition on the kinetics of the copolymerization, especially on f int . The copolymer composition did not suffer a deviation from the Mayo−Lewis equation in the initial period, as seen in other controlled radical copolymerizations.…”
Section: Introductionmentioning
confidence: 99%